2018
DOI: 10.1007/s11356-018-2932-z
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Talitrus saltator (Crustacea, Amphipoda): new evidence of ingestion from natural contexts

Abstract: Using Fourier transform infrared spectroscopy (FT-IR) measurements and comparing the spectrum peaks (range 4000-600 cm) with reference spectra database and instrument libraries, we observed new evidence of the ingestion of microplastic particles analyzing the digestive tracts of Talitrus saltator. Specimens, sampled in central Italy, probably ingested the particles with natural detritus. Since worldwide many species of invertebrates and vertebrates (e.g., birds) feed on Amphipoda along coastal ecosystems, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Thus, it has been shown that larger invertebrate species ingest microplastics, mistaking them for their natural prey because of similarities in shape, size and color, e.g., mistaking them for plankton [66]- [73]. There is some worry that microplastics accumulate along the food chain [74] [75] [76] with the accumulation of microplastics in the digestive tract of Talitrus saltator (Crustacea, Amphipoda), a species which is heavily fed upon by birds, given as an example [77]. Lastly, there is also the worry that ultimately microplastics can Diversity (CBD) reported that man-made marine litter has known negative impacts on 663 species studied [90].…”
Section: Composition Of Microplastics Their Distribution In the Envimentioning
confidence: 99%
“…Thus, it has been shown that larger invertebrate species ingest microplastics, mistaking them for their natural prey because of similarities in shape, size and color, e.g., mistaking them for plankton [66]- [73]. There is some worry that microplastics accumulate along the food chain [74] [75] [76] with the accumulation of microplastics in the digestive tract of Talitrus saltator (Crustacea, Amphipoda), a species which is heavily fed upon by birds, given as an example [77]. Lastly, there is also the worry that ultimately microplastics can Diversity (CBD) reported that man-made marine litter has known negative impacts on 663 species studied [90].…”
Section: Composition Of Microplastics Their Distribution In the Envimentioning
confidence: 99%
“…With the establishment of the protected area, most of the research was directed to the knowledge of flora, vegetation, fauna and other ecosystem components (Battisti, 2006a), and partly included in the activities of the local research station settled by LTER -Long Term Ecological Research (Bertoni, 2012). More specifically, this site has been the subject of studies on microphytes (diatoms: Della Bella et al, 2006Bella et al, , 2007, macrophytes (Guidi, 2006;Buccomino & Leporatti, 2009;Nimis et al, 2020;specific research and reviews: Lucchese, 1996;Aglitti et al, 2006;Fanelli, 2006;Santoro et al, 2012;Acosta et al, 2013;Del Vecchio et al 2018;Ioni et al, 2020;floristic notes: Bartolucci & Iocchi, 2007;Anzalone et al, 2010;Fanelli et al, 2011;Fabrini, 2019), microfaunal benthos (Foraminifera, Ostracoda and others: Nicoletti et al, 2006;Raffi et al, 2018;Di Bella et al, 2020), freshwater macro-benthos (Gramegna et al, 2006), Crustacea Amphipoda (Iannilli et al, 2018), non-native Crustacea (Chiesa, 2006;Chiesa et al, 2006;Scalici et al, 2009;Scalici et al, 2010), freshwater and terrestrial Mollusca (Minganti & Zocchi, 2006), marine Mollusca (Pessolano et al, 2006; notes: e.g. Amati et al, 2019;Amati et al, 2020;Battisti, 2020;Giannuzzi-Savelli et al, 2020), Chilopoda (Zapparoli, 2006), Hymenoptera (Di Giovanni & Reshchikov, 2016), Odonata…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many invertebrates feed on natural wrack, playing a crucial role in the recycling of nutrients in coastal habitats [64,65]. On the other hand, some studies proved that wrack consumers can ingest marine plastic litter accumulated on wrack [66,67]. Other animals can feed on the wrack consumers [3,68], so the presence of plastics and toxic elements (i.e., cigarette butts) in this natural wrack could also promote cascading effects on the food chain.…”
Section: Discussionmentioning
confidence: 99%